Academic Ethics and Moral Agency in EFL Writing: Census-Based Evidence from a Rural Vocational School on the West Sumatra-Riau Border - Geby Adrian; Darmansyah; Maisarah Mitra Adrian (SALEE: Study of Applied Linguistics and English Education, 2026)
Academic ethics and moral agency are central to EFL writing, yet they remain underexamined in rural vocational schools where students often face limited linguistic, academic, and digital literacy support. This study examines academic ethics and moral agency in EFL writing among students at a small rural vocational school located on the West Sumatra-Riau border, Indonesia. Using an explanatory sequential mixed-method design, the study first conducted a census-based survey involving all 74 students, followed by interviews to explain the quantitative patterns. The findings showed moderate levels of academic ethics (M = 3.187, SD = 0.330) and moral agency (M = 3.182, SD = 0.350). Spearman correlation indicated a significant positive association between academic ethics and moral agency (? = .476, p < .001). Bootstrapped regression showed that academic ethics positively predicted moral agency (B = .599, 95% CI [.340, .834], R² = .319). Interview data revealed barriers related to limited vocabulary, weak grammar, translation-tool dependence, uncertain citation practices, copy-paste habits, and unequal group participation. The study contributes context-bound evidence that moral awareness in EFL writing does not automatically lead to ethical enactment. It argues for explicit, scaffolded, and context-sensitive writing ethics instruction in rural vocational EFL classrooms.